2022
DOI: 10.1177/1351010x211068850
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the acoustic environment on human emotion and experience: A case study of worship spaces

Abstract: People’s interactions with the environment shape their experiences. Thus, understanding these interactions is critical to enhancing human well-being. Aural attributes play a significant role in shaping the perception of space in addition to visual attributes. It is well known that sounds evoke an emotional response, but less is known about how the acoustic characteristics of environments reinforce such an emotional impact. By adopting virtual reality as a platform for recreating 3D sounds and 360° visuals of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 45 publications
(59 reference statements)
0
20
0
Order By: Relevance
“…'Nostalgia' may have a mixed valence (Batcho, 2020), while 'Wonder' and 'Transcendence' are under-researched from a valence-arousal perspec�ve. Algargoosh et al (2022) found effects for similar emo�ons when a room acous�c was applied to a recording, compared against an anechoic condi�on -including 'Nostalgic' and 'Spiritual'. In Mo et al (2016), 'Mysterious' and Reverbera�on Time and Musical Emo�on 'Roman�c' were associated with higher reverbera�on and are again difficult to map onto valence-arousal dimensions.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…'Nostalgia' may have a mixed valence (Batcho, 2020), while 'Wonder' and 'Transcendence' are under-researched from a valence-arousal perspec�ve. Algargoosh et al (2022) found effects for similar emo�ons when a room acous�c was applied to a recording, compared against an anechoic condi�on -including 'Nostalgic' and 'Spiritual'. In Mo et al (2016), 'Mysterious' and Reverbera�on Time and Musical Emo�on 'Roman�c' were associated with higher reverbera�on and are again difficult to map onto valence-arousal dimensions.…”
Section: Discussionmentioning
confidence: 92%
“…Other studies have related valence-arousal ra�ngs to source type and mo�on in an acous�c se�ng (Hagman, 2010;Tajadura-Jiménez et al, 2010b). In addi�on to 'impact' and valence-arousal, effects have been found across some more fine-grained emo�on categories (Algargoosh et al, 2022;Mo et al, 2006 -see Table 1).…”
Section: Room Acous�cs and Musical Emo�on In Recorded Music Listeningmentioning
confidence: 95%
See 3 more Smart Citations